Blockchain based framework for educational certificates verification - Saleh, Omar S.; Ghazali, Osman; Rana, Muhammad Ehsan (Advance Scientific Research, 2020)
Document verification is a complex domain that involves various challenging and tedious processes to authenticate. Moreover various types of documents for instance banking documents, government documents, transaction documents, educational certificates etc. might involve customized verification and authentication practices. The content for each type vary significantly, hence requires to be dealt in a distinct manner. For students, educational certificates are the most important documents issued by their universities. However, as the issuing process is not that transparent and verifiable, fake certificates can be easily created. A skil fully generated fake certificate is always hard to detect and can be treated as the original. With the increase of forged documents, credibility of both the document holder and the issuing authority is jeopardized. Blockchain technology has recently emerged as a potential mean for authenticating the document verification process and a significant tool to combat document fraud and misuse. This research aimed to enhance the document verification process using blockchain technology. In this research, authors have identified the security themes required for document verification in the blockchain. This research also identifies the gaps and loopholes in the current blockchain based educational certificate verification solutions. At the end, a blockchain based framework for verifying educational certificates focusing on themes including authentication, authorization, confidentiality, privacy and ownership is proposed using the Hyperledger Fabric Framework.